MITOS KECANTIKAN DALAM CERPEN-CERPEN DWI RATIH RAMADHANY - Royyan Julian (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This study highlights the myth of beauty in short stories written by Dwi Ratih Ramadhany, which are “Janda Sungai Gayam” and “Perempuan Bisu dan Cermin Ratu”. The perspective utilized in this study is the myth of beauty by Naomi Wolf. The results are: (1) both the short stories illustrate standards of beauty identified by long black hair, long neck, sensual lips, body fragrant, white-toned-smooth-skin, and slim body; (2) in both short stories, the quality of beauty refers to behaviors that could arouse an excitement rather than merely consider physical appearance;(3) regarding beauty not as an intrinsic quality, it is affected by external factors, for instance cosmetic and supernatural powers. Myth of beauty in both short stories stands on the runway of men’s interest and taste, and women’s motive toachieve resources provided by men, which are called loyalty, recognition, praise and charm.Kajian ini mengangkat isu mitos kecantikan dalam cerpen-cerpen Dwi Ratih Ramadhany, yakni